2010
DOI: 10.1002/esp.1962
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale sediment bodies and superimposed bedforms on the continental shelf close to the Strait of Gibraltar: interplay of complex oceanographic conditions and physiographic constraints

Abstract: A previously unknown fi eld of large-scale sedimentary bodies has been mapped and studied on the continental shelf off the Cape Trafalgar near the Strait of Gibraltar with particular emphasis on the relationship between large-scale sediment bodies and the superimposed bedforms. This study is based on a grid of 975 km of high-resolution seismic profi les collected at water depths ranging between 15 and 60 m.High variability of large-scale sedimentary bodies is attributed to the complex interaction of hydrodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…They show that as the salt wedge density underflow migrates upstream and passes from a flat bed to dune roughness, the underflow becomes both in-phase with the bedforms and supercritical. Lobo et al (2010) also use the internal structure of large-scale sand banks and superimposed bedforms to assist in understanding their formation and dynamics. Such interactions between dunes and density flows are argued to be dependent on the friction Richardson number, internal Froude number and relative bedform height, that define the effective 'blockage' presented by the roughness to the stratified flow.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…They show that as the salt wedge density underflow migrates upstream and passes from a flat bed to dune roughness, the underflow becomes both in-phase with the bedforms and supercritical. Lobo et al (2010) also use the internal structure of large-scale sand banks and superimposed bedforms to assist in understanding their formation and dynamics. Such interactions between dunes and density flows are argued to be dependent on the friction Richardson number, internal Froude number and relative bedform height, that define the effective 'blockage' presented by the roughness to the stratified flow.…”
Section: Introductionmentioning
confidence: 99%
“…Once this occurs, flow mixing is shown to be greatly enhanced, and dominates mixing of the current in comparison to that generated by shear at the top of the flow. Lobo et al (2010) detail the high level of variability in the size and scales of these larger sand banks, and relate this to the complex interactions between two currents moving in differing directions. Future investigations of the interaction between form-induced roughness and density stratification may prove a very useful environment in which to investigate the topology and effects of such large-scale macroturbulence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Off (1963) believed there should be a relation between sand waves and tidal current ridges, however, due to a lack of accurate surveys, this relation could not be quantified. Further work on tidal ridges similarly hypothesized that offshore tidal ridges are made from the accretion of cross-beds formed by dunes (Lobo et al, 2010;Reynaud and Dalrymple, 2012). More recently, Lefebvre et al (2013) suggested that smaller bedforms may be influencing the dunes on which they reside.…”
Section: Introductionmentioning
confidence: 99%